Urban land economics - Balchin, Paul N.; Kieve, Jeffrey L. (London : Macmillan, 1977)
After a general introductory discussion of the main characteristics of land, the book considers the location of urban land-uses and spatial structures and urban growth.
Includes bibliographical references: p. [262]-263 and index.
oif 04/03/2019
Loans
Keywords: Land use, Urban; Urban economics; City planning